1990
DOI: 10.1159/000125310
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine Disrupts Estrous Cyclicity and Alters the Reproductive Neuroendocrine Axis in the Rat

Abstract: Although a common drug of abuse, cocaine’s effects on cyclic reproductive functions and the neuroendocrine systems regulating these functions have not been studied. Here, we report the effects of cocaine on (1) estrous cyclicity and ovulation rates and (2) the stimulated in vitro release of hypothalamic GnRH and aminergic neurotransmitters directly involved in regulating or modulating GnRH release. Within 7 days of treatment with 10 mg kg–1 day–1 of cocaine HC1 subcutaneously, rats demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…While suggestive, our results are limited in that they cannot fully account for the complex interactions of endogenous ovarian hormones as they fluctuate across the cycle in intact animals. It should also be noted that while estradiol may have played a role in mediating reinstatement in the current study, it is also important to note that chronic cocaine exposure has been shown to disrupt estrous cycle activity in primates and rodents (Grimm and See 1997; King et al 1990; Mello et al 1997), with previous work in our laboratory demonstrating a decline in the estradiol peak of proestrus during and following chronic cocaine self-administration (Feltenstein and See 2007). Moreover, plasma levels of hormones do not necessarily indicate neuronal alterations that may occur in response to changes in endogenous hormone levels.…”
Section: Discussionmentioning
confidence: 70%
“…While suggestive, our results are limited in that they cannot fully account for the complex interactions of endogenous ovarian hormones as they fluctuate across the cycle in intact animals. It should also be noted that while estradiol may have played a role in mediating reinstatement in the current study, it is also important to note that chronic cocaine exposure has been shown to disrupt estrous cycle activity in primates and rodents (Grimm and See 1997; King et al 1990; Mello et al 1997), with previous work in our laboratory demonstrating a decline in the estradiol peak of proestrus during and following chronic cocaine self-administration (Feltenstein and See 2007). Moreover, plasma levels of hormones do not necessarily indicate neuronal alterations that may occur in response to changes in endogenous hormone levels.…”
Section: Discussionmentioning
confidence: 70%
“…Estradiol administration has been shown to increase the reinforcing effects of psychostimulants in humans (Justice and de Wit, 2000) and enhance the acquisition (Lynch et al, 2001; Hu et al, 2004; Jackson et al, 2006) and escalation (Larson et al, 2007) of cocaine self-administration in rats, with plasma estradiol levels showing a positive correlation with cocaine-seeking (Lynch, 2008). However, while endogenous plasma estradiol levels are enhanced during proestrus in drug-free females, this estradiol peak is not consistently seen after chronic cocaine self-administration (Feltenstein and See, 2007), due to cocaine's disruption of normal estrous cycle activity (King et al, 1990, 1993; Grimm and See, 1997; Mello et al, 1997). Thus, while elevated plasma estradiol during proestrus may have enhanced the reinforcing effects of cocaine early in self-administration, cocaine's disruption of estradiol following chronic cocaine exposure may reduce the impact of this hormone in enhancing cocaine self-administration.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the preclinical literature, we had anticipated that female cocaine abusers would have had abnormal menstrual cycles. Several studies have shown that chronic cocaine use disrupts various aspects of the estrous cycle in rodents (King et al 1990(King et al , 1993Chen and Vandenbergh 1994;Quiñones-Jenab et al 2000a; but see Booze et al 1999) and the menstrual cycle in nonhuman primates (Mello et al 1997;Potter et al 1998Potter et al , 1999 and humans (Mello 1998). In the present study, women reported spending approximately US $400 per week on cocaine and using it 3-4 days each week.…”
Section: Discussionmentioning
confidence: 99%